Variations in leaf traits modulate plant vegetative and reproductive phenological sequencing across arid Mediterranean shrublands. - Navarro-del-Águila, María Teresa; Hidalgo-Triana, Noelia (Frontiers, 2021)
Structural and nutrient traits of a leaf are important for understanding plant ecological strategies (e.g., drought avoidance). We studied the specific leaf area (SLA), leaf carbon content (LCC), leaf nitrogen content (LNC), leaf phosphorous content (LPC), and the phenophase sequence index (PSI) in 126 Mediterranean perennial species from predesert (SMS) and semiarid (SaMS) to subalpine (SAS), alpine cushion (AcS), and oro-Mediterranean (AjS) shrublands, which represent eight functional groups (evergreen and deciduous trees, evergreen large and half shrubs, deciduous large and half shrubs, succulents and perennial herbs). We analyzed the variation and relationships between leaf traits and PSI among shrublands, functional groups, and within species with drought-avoidance mechanisms. SLA variation of 20–60% could be ascribed to differences between functional groups and only 38–48% to different shrublands increasing from the predesert to the alpine. Alpine species display low PSI and N:P and high SLA, LNC, LPC, LCC, and C:N. On the contrary, predesert and semiarid showed high PSI and low SLA. SLA mediates the vegetative and reproductive phenological plant sequencing, high SLA is often associated with the overlapping in growth and reproductive phenophases with a seasonal reduction of vegetative growth, whereas low SLA is associated with vegetative and reproductive sequencing and a seasonal extension of vegetative growth. Species with drought-avoidance mechanisms (e.g., semideciduous species) contribute to an increase in the mean values of the SLA and LNC because these species show similar leaf and phenological patterns as the deciduous (high SLA and LNC and low PSI). The N:P indicates that only the alpine shrublands could present P limitations. The positive correlations between SLA and LPC and LNC and LPC (leaf economic spectrum) and the negative correlation between SLA and C:N were consistently maintained in the studied arid Mediterranean shrublands.
Keywords: Clima mediterráneo; Hojas (Botánica); Nitrógeno; Fósforo; Plantas vivaces; Estequiometría; Mediterranean climate; Leaf economics spectrum; Nitrogen; Phosphorus; Perennial species; Phenophase sequence index; Specific leaf area; Stoichiometry